Detection of bla NDM-1 Encoding Imepenemase among the Imipenem-Resistant Gram-Negative Bacilli Isolated from Various Clinical Samples at a Tertiary Care Hospital of Eastern Nepal: A Descriptive Cross-Sectional Study - S. Gautam; N. R. Bhattarai; K. Rai; A. Poudyal; B. Khanal (International Journal of Microbiology)
Background. Carbapenem resistance among Gram-negative isolates caused by the production of the metallo-β-lactamase (MBL) enzyme is being increasingly reported worldwide. One of the newly emerged metallo-β-lactamases is New Delhi metallo-β-lactamase. Data regarding its occurrence in hospital setting and percentage prevalence among different Gram-negative bacterial isolates are lacking in our part. This study has been undertaken for determining the presence of the bla NDM-1 gene among the clinical isolates of imipenem-resistant Gram-negative bacteria in a tertiary care center in Dharan, Nepal. Methods. A total of 75 imipenem-resistant Gram-negative isolates were studied. These were screened for metallo-β-lactamase (MBL) production by phenotypic assays such as double-disc synergy test (DDST) and combined disc diffusion test (CDDT). PCR was performed for the molecular detection of gene NDM-1. Ten-disc method was performed to detect the presence of ESBL, AmpC, carbapenamase, and K1 β-lactamase production. Results. Using the molecular method, bla NDM-1 was detected in 36% of the isolates. Phenotypically, double-disc synergy test (DDST) and combined disc diffusion test (CDST) detected MBL production in 38.7% and 37.3% of the isolates, respectively. Ten-disc method detected ESBL in 26.6% of the isolates, but none of the isolates was found to be AmpC, carbapenamase, and K1 β-lactamase producers. Conclusion. A high percentage of the NDM-1 producer was noted among imipenem-resistant GNB. Apart from performing only antimicrobial sensitivity test, phenotypic and molecular screening should be employed to find out the actual number of metallo-β-lactamase producers and the existence of the resistance gene.